Pengalaman dalam Penegakkan Diagnosis Neuronal Ceroid Lipofuscinosis Tipe-2 - Gultom, Lanny Christine; The, Valensia Vivian (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Developmental regression is always an alarming symptom in children as it is an early sign of some genetic disorders, one of which is neuronal ceroid lipofuscinosis (NCL). NCL is a group of rare neurodegenerative disorder caused by accumulation of intracellular ceroid lipofuscin. Since 2017 an enzyme replacement therapy (ERT) has been approved by Food and Drug Administration (FDA) for this disease. The symptoms of NCL could be managed by ERT if detected early, and the child could live normally.Case: We present a case of a 6-year-and-5-month-old boy with developmental regression, speech delay, recurrent seizure, and visual impairment, who was diagnosed with NCL type 2 after genetic testing. Compound heterozygous mutations in tripeptidyl-peptidase 1 (TPP1) gene was revealed, consistent with very low level of TPP1 enzyme in this patient.Discussion: NCL is a fatal disease which is often misdiagnosed in early stage. Diagnostic delay of NCL often occurs due to lack of awareness which often leads to premature death.Conclusion: Knowledge regarding the disease is important for early detection and to slow down the disease progression.